WAVELET-BASED CORRELATION (WBC) OF ZONED CRYSTAL POPULATIONS AND MAGMA MIXING - Wallace G.S.; Bergantz G.W. (My University, 2002)
Magma mixing is a common process and yet the rates, kinematics and numbers of events are difficult to establish. One expression of mixing is the major, trace element, and isotopic zoning in crystals, which provides a sequential but non-monotonic record of the creation and dissipation of volumes of distinct chemical potential. We demonstrate a wavelet-based correlation (WBC) technique that uses this zoning for the recognition of the minimum number of mixing, or open-system events, and the criteria for identifying populations of crystals that have previously shared a mixing event. When combined with field observations of the spatial distribution of crystal populations, WBC provides a statistical link between the time-varying thermodynamic and fluid dynamic history of the magmatic system. WBC can also be used as a data mining utility to reveal open-system events where outcrop is sparse. An analysis of zoned plagioclase from the Tuolumne Intrusive Suite provides a proof of principle for WBC.
Keywords: MAGMA CHAMBERS; MAGMA TRANSPORT; CRYSTAL ZONING; MIXING; WAVELETS